Analysis of the Effect of Congestion Control DCCP CCID 2 on TCP SACK - Bambang Sugiantoro; Izza Afkarina (Seminar Nasional Informatika (SEMNASIF), 2021)
Purpose: Observing the effect of DCCP CCID 2 congestion control on TCP traffic using the NS-2 simulator.Design/methodology/approach: Using TCP-SACK with performance testing parameters observed are congestion window, throughput, and packet drop.Findings/result: DCCP CCID 2 is more able to maximize bandwidth than TCP SACK because TCP SACK has a retransmit phase where if a packet is lost, the lost packet will be sent back which can cause delays. The buffer size also does not affect the throughput value of TCP SACK because TCP SACK and DCCP CCID 2 have the same congestion control mechanism and the congestion control algorithm CCID 2 is more advanced.Originality/value/state of the art: This study observes the effect of DCCP CCID 2 congestion control on TCP traffic, where the TCP SACK variation used in this study has never been used before.